Microcin J25-Ga induces apoptosis in mammalian cells by inhibiting mitochondrial RNA-polymerase - Niklison Chirou, Maria Victoria (2011)
MccJ25, an antimicrobial peptide, was unable to cause apoptosis of COS-7 cells in spite of inducing reactive-oxygen species overproduction as well as cytochrome c release from isolated mitochondria. Surprisingly, MccJ25-Ga, an amidated variant of MccJ25 that displays similar anti-mitochondrial effects, did induce apoptosis in COS-7. The only difference found between the activities of these peptides was the unpredicted inhibition of mitochondrial RNA synthesis by MccJ25-Ga. These results led us to hypothesize that both mitochondrial RNA polymerase and mitochondrial membrane might be the molecular targets of MccJ25-Ga in mitochondria and this combined effect may lead to apoptosis. Surprisingly, MccJ25-Ga, an amidated variant of MccJ25 that displays similar anti-mitochondrial effects, did induce apoptosis in COS-7. The only difference found between the activities of these peptides was the unpredicted inhibition of mitochondrial RNA synthesis by MccJ25-Ga. These results led us to hypothesize that both mitochondrial RNA polymerase and mitochondrial membrane might be the molecular targets of MccJ25-Ga in mitochondria and this combined effect may lead to apoptosis. Surprisingly, MccJ25-Ga, an amidated variant of MccJ25 that displays similar anti-mitochondrial effects, did induce apoptosis in COS-7. The only difference found between the activities of these peptides was the unpredicted inhibition of mitochondrial RNA synthesis by MccJ25-Ga. These results led us to hypothesize that both mitochondrial RNA polymerase and mitochondrial membrane might be the molecular targets of MccJ25-Ga in mitochondria and this combined effect may lead to apoptosis. c release from isolated mitochondria. Surprisingly, MccJ25-Ga, an amidated variant of MccJ25 that displays similar anti-mitochondrial effects, did induce apoptosis in COS-7. The only difference found between the activities of these peptides was the unpredicted inhibition of mitochondrial RNA synthesis by MccJ25-Ga. These results led us to hypothesize that both mitochondrial RNA polymerase and mitochondrial membrane might be the molecular targets of MccJ25-Ga in mitochondria and this combined effect may lead to apoptosis.